In-situ radon-in-water detection for high resolution submarine groundwater discharge assessment - Zhao, Shibin; Li, Meng; Burnett, William C.; Cheng, Kai; Li, Chunqian; Guo, Jinjia; Yu, Songling; Liu, Wen; Yang, Tong; Dimova, Natasha T.; Chen, Guangquan; Yu, Zhigang; et al. (Frontiers in Marine Science, 2022)
Submarine groundwater discharge (SGD), including both land-based fresh groundwater that enters the ocean from coastal aquifers as well as recirculated seawater that is continuously recharged and discharged on the seabed, has been considered as an important component of the global water and biogenic element (e.g., nitrogen, phosphorus, silicon and carbon) sources and a significant pathway for material exchange at the land-sea interface of coastal ecosystems. Some researchers reported that SGD associated nutrient additions to coastal waters have caused unwanted ecological issues, including red tides, coastal acidification and hypoxia. Natural radon isotope (222Rn, t1/2 = 3.8 d) is an excellent tracer for studying SGD and other oceanographic processes including air-sea gas exchange, sediment-water diffusion, and earthquake prediction. However, the conventional radon measurement methods suffer many technical disadvantages. We consequently developed a convenient submersible radon determination approach (“OUC-Rn”) using a commercial pulsed ionization chamber (PIC) radon sensor and gas extraction membrane module to produce high precision and high resolution observations. We demonstrate the radon degassing efficiency of the membrane contactor is comparable to the shower-head type air-water exchanger but is independent of operating position. The radon measurement efficiency of the PIC is 2-fold higher than the RAD7 detector and is far less influenced by moisture. We successfully deployed the system in 2.5 meters water depth over a 100 hours period in an anthropogenic influenced bay. Based on our high temporal resolution observations, the SGD flux was estimated to be 0-43.0 cm/d (mean: 25.4 ± 14.5 cm/d). The SGD fluxes pattern plotted together with the tidal variations revealed that tidal pumping may be the main force driving seawater recirculation into aquifers and thus affecting nutrient, carbon and other dissolved matters dynamics in coastal regions.